ROOT HAIR DEFECTIVE SIX-LIKE4 (RSL4) promotes root hair elongation by transcriptionally regulating the expression of genes required for cell growth - Vijayakumar, Priya (The New phytologist, 2016)
© 2016 The Authors. New Phytologist © 2016 New Phytologist Trust.